2014
DOI: 10.5194/bg-11-6265-2014
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope biogeochemistry of lakes along a trophic gradient

Abstract: Abstract. The stable carbon (C) isotope variability of dissolved inorganic and organic C (DIC and DOC), particulate organic carbon (POC), glucose and polar-lipid derived fatty acids (PLFAs) was studied in a survey of 22 North American oligotrophic to eutrophic lakes. The δ 13 C of different PLFAs were used as proxy for phytoplankton producers and bacterial consumers. Lake pCO 2 was primarily determined by autochthonous production (phytoplankton biomass), especially in eutrophic lakes, and governed the δ 13 C o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 62 publications
7
27
1
1
Order By: Relevance
“…In total 22 lakes were examined, 10 from the U.S. state of Iowa and 12 from the state of Minnesota (Table ). These lakes have previously been assigned as either eutrophic lakes (all of the Iowa lakes plus the Minnesota lake Little Splithand, n = 11) or oligo‐mesotrophic lakes (all remaining Minnesota lakes, n = 11) based on their average summer total P (TP) concentration as described in de Kluijver et al (). The trophic state of the eutrophic lakes is caused by high nutrient loads from agricultural run‐off (Arbuckle and Downing ), while the oligo‐mesotrophic lakes in the forested area of Minnesota are relatively pristine in nature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total 22 lakes were examined, 10 from the U.S. state of Iowa and 12 from the state of Minnesota (Table ). These lakes have previously been assigned as either eutrophic lakes (all of the Iowa lakes plus the Minnesota lake Little Splithand, n = 11) or oligo‐mesotrophic lakes (all remaining Minnesota lakes, n = 11) based on their average summer total P (TP) concentration as described in de Kluijver et al (). The trophic state of the eutrophic lakes is caused by high nutrient loads from agricultural run‐off (Arbuckle and Downing ), while the oligo‐mesotrophic lakes in the forested area of Minnesota are relatively pristine in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, oligo‐mesotrophic lakes, where DOC concentrations are equal to or higher than POC concentrations, have been shown to be dominated by heterotrophic bacterial processes compared to eutrophic lakes (Biddanda et al ). de Kluijver et al () reported the concentration of phytoplankton derived C (C phyto , based on chlorophyll a concentration and summed concentration of phytoplankton derived FAs) and bacterial derived C (C bac , based on the summed concentration of bacterial specific FAs) for the Iowa and Minnesota lakes. The ratio of C bac to C phyt was indeed higher in the Minnesota lakes (av.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations